1995
DOI: 10.1111/j.1432-1033.1995.442_2.x
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency of Glycerol 2‐Phosphate and sn ‐Glycerol 3‐Phosphate as Nucleotidyl Acceptors in Snake Venom Phosphodiesterase Esterifications

Abstract: Snake venom phosphodiesterase (SVP) catalyzes the alcoholysis of ATP by primary R-CH,OH alcohols with uncharged R residues, yielding AMP-0-CH,R esterification products. The alcohols compete with water for an SVP-bound adenylyl intermediate. In this study, it has been shown that SVP also catalyzes the reactions of glycerol 2-phosphate and sn-glycerol 3-phosphate with ATP to yield AMP-Oglycerophosphoryl esters. The products were identified by HPLC, the dependency of the reactions on glycerol phosphates, ultravio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…For those reasons, AppA was used as the substrate, instead of ATP, employed in studies of SVP-catalyzed alcoholysis (García-Díaz et al, 1993;Vergeles et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For those reasons, AppA was used as the substrate, instead of ATP, employed in studies of SVP-catalyzed alcoholysis (García-Díaz et al, 1993;Vergeles et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…SVP reactions in alcohol-water mixtures have been studied only at pH 7.5 and 37°C (García-Díaz et al, 1993;Vergeles et al, 1995). To elucidate whether pH and temperature effects on PNP could be a general feature of nucleotide pyrophosphatases, their effects on SVP were also studied.…”
Section: Solvolytic Behavior Of Svp: Unaffected By Ph and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…It was obtained in a partially purified form, which generated several protein bands when analysed by SDS\PAGE or by native gel electrophoresis stained with Coomassie Blue, but only one band was produced when native gels were stained for NPP\PDE activity with either 2-naphthyl phenylphosphonate [28] or 1naphthyl-5h-dTMP [29] (Sigma, Madrid, Spain) as the substrate. Other materials were from sources reported previously [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…the basis of the knowledge that snake venom and mammalian NPP\PDE enzymes catalyse a double nucleophilic displacement on the α-phosphorus atom of the adenylyl moiety of ATP : a threonine lateral chain carries out first an attack that leads to an adenylyl-enzyme intermediate ; thereafter, a molecule of water splits the phosphodiester linkage of this intermediate, releasing AMP as a product of hydrolysis [16,[19][20][21][22][23]. In this mechanism, one may ask whether, in the active centre of mammalian NPP\PDE, alcohols could substitute for water, as is known to occur in the active centre of snake venom NPP\PDE [24][25][26]. From the present study, rat NPP\PDE has been identified as a more efficient adenylyl transferase than the snake enzyme, with an active centre capable of establishing multiple interactions with specific alcohol acceptors of the enzyme-bound adenylate.…”
Section: Introductionmentioning
confidence: 99%